A Solvent-free Method for Synthesis of Dihydroangelicins using Microwaves - M. Ruiz, Diego; C. Autino, Juan; P. Romanelli, Gustavo (Current Green Chemistry, 2016)
Background: Dihydrofurocoumarins are a large family of compounds, among them, dihydroangelicins and dihydropsoralens, are present in various plant species with varied biological activity. Several strategies have been developed for synthesizing these compounds and various catalysts have been used for this purpose. Methods: In this work, we report the synthesis of 8,9-dihydrofuran [2, 3-h] coumarins using allyloxycoumarin cycloaddition in sustainable conditions: absence of solvents, application of microwave radiation, and insoluble acid catalysis by means of heteropolyacids with Preyssler structure, [H14(NaP5MoW29O110)]. Conclusion: With these conditions, and testing sustainability by means of Eco-Scale and E-factor, we replace the use of solvents and mineral acids having a great impact on the environment with a solid, easily recoverable heteropolyacid.
Keywords: green chemistry